Analysis on Wearable Antenna Performance on Different Radiating Elements for GPS Application - Nordin, M.S. Amin; Abd Rahman, N. H.; Ali, M. T.; Zaidi, N. I.; Ahmad, M. R. (International Journal of Integrated Engineering, 2020)
This paper presents a study on the performance of self-manufactured electro-textile (SME-T) antenna that was designed at 1.575 GHz based on the allocated spectrum for Global Positioning System (GPS) application. However, due to its known low-conductivity characteristic, the ability of the newly developed material to perform as a good antenna shall be verified. Therefore, the performance of the antennas are compared and studied with respect to established materials such as adhesive copper tape and commercial conductive fabric named SHIELDITTM as the radiating elements. Here, four e-textile antennas having approximately the same size are fabricated and tested. The performance of all antennas, in terms of return loss, radiation pattern, gain, and efficiency; manufactured by using different radiating elements, such as copper, SHIELDITTM and SME-T fabricated on polyester fabric as the substrate are analyzed. The measured return loss and radiation pattern of SME-T antenna has proven that the antenna is well suited for wearable application. The measured antenna gain and efficiency of 0.61 dB and 25.95% are obtained and it is proven that the fabricated SME-T antenna can act as a receiving antenna designed for GPS applications which requires low gain antenna for passive monitoring.